An analysis of the completeness of referral forms and cases evaluated by an oral medicine specialized service - Dutra Guzenski, Bianca; Casotti, Thiago Tomazetti; Strey, Jessica Rodriguez; Martins, Manoela Domingues; Rados, Pantelis Varvaki; Carrard, Vinicius Coelho (Clinical and Biomedical Research, 2021)
Introduction: Oral lesions are present in approximately 30% of the population worldwide. Although the mouth is an anatomical region that can be easily accessed for direct visual examination, most dentists of dental surgeons have reported difficulties in the diagnosis and management of oral diseases. Objective: The primary aim of this study was to assess the completeness of referral forms of the patients referred from the primary care to an Oral Medicine service. The secondary aim was to analyze if the complexity of the cases justify the referral to a specialist. Methods: Data from 131 referral forms of patients referred from June 2014 to April 2016 were retrieved from the records. The referral’s completeness analysis comprised two stages. Stage 1 mainly comprised patient and applicant’s information. In the Stage 2, the documents were scored according to amount of information, including the description of the lesion characteristics and the procedures required for the patients’ diagnosis and management. The referral was considered justifiable if some procedures not available at primary care were required for diagnosis or treatment. Results: Five (9.8%) referral forms were considered well filled. Diagnosis agreement was 71.4%. In regards to the need of referral, 40,6% of the cases (n=50) could be settle at the primary care. Conclusion: In conclusion, few referral forms had high-quality information and the many cases could be managed at primary care health services.